2013
DOI: 10.1515/sagmb-2012-0067
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of chemometrics-based feature selection methods in early cancer detection and biomarker discovery

Abstract: In omics studies aimed at the early detection and diagnosis of cancer, bioinformatics tools play a significant role when analyzing high dimensional, complex datasets, as well as when identifying a small set of biomarkers. However, in many cases, there are ambiguities in the robustness and the consistency of the discovered biomarker sets, since the feature selection methods often lead to irreproducible results. To address this, both the stability and the classification power of several chemometrics-based featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In biomedical fields, this is a proxy for reproducible research, in the latter case indicating that the biological features the method has found are likely to be a data artifact, not a real clinical signal worth pursuing with further resources (Lee et al. , 2013 ). Goh and Wong ( 2016 ) recommend augmenting statistical feature selection methods with concurrent analysis on stability and reproducibility to improve the quality of selected features prior to experimental validation (Sze and Schloss, 2016 ; Duvallet et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In biomedical fields, this is a proxy for reproducible research, in the latter case indicating that the biological features the method has found are likely to be a data artifact, not a real clinical signal worth pursuing with further resources (Lee et al. , 2013 ). Goh and Wong ( 2016 ) recommend augmenting statistical feature selection methods with concurrent analysis on stability and reproducibility to improve the quality of selected features prior to experimental validation (Sze and Schloss, 2016 ; Duvallet et al.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, if small changes to the data result in significantly different feature subsets, then this method is considered unstable, and we should not trust the output as reflective of the true underlying structure influencing the outcome being predicted. In biomedical fields, this is a proxy for reproducible research, in the latter case indicating that the biological features the method has found are likely to be a data artifact, not a real clinical signal worth pursuing with further resources (Lee et al, 2013). Goh and Wong (2016) recommend augmenting statistical feature selection methods with concurrent analysis on stability and reproducibility to improve the quality of selected features prior to experimental validation (Sze and Schloss, 2016;Duvallet et al, 2017).…”
Section: Estimation Of Stabilitymentioning
confidence: 99%
“…According to (Nogueira, Sechidis, and Brown, 2018) the measurement of stability addresses the question — how much we can trust the algorithm? From biomedical standpoint, it is crucial to guarantee the reproducibility of the given feature selection methods when finding proper sets of biomarkers (Lee et al, 2013)…”
Section: Introductionmentioning
confidence: 99%
“…in bioinformatics applications -if the alteration/exclusion of just one training example results in a very different choice of biomarkers, we cannot justifiably say the FS is doing a reliable job. In early cancer detection, stability of the identified markers is a strong indicator of reproducible research [6], [12] and therefore selecting a stable set of markers is said to be equally important as their predictive power [7].…”
Section: Introductionmentioning
confidence: 99%